Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Guru Smk Bhakti Kencana Tasikmalaya - Silvi Indah Pratiwi; Askolani Askolani; Kusuma Agdhi Rahwana (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine the effect simultaneously or partially of the variables Work Motivation and Work Discipline on Performance measured The population used in this study were 45 teachers at SMK Bhakti Kencana. The method used in this research is descriptive research with a quantitative approach. Sample selection using saturated samples. The sample used was the entire population, namely 45 Bhakti Kencana Vocational School teachers. Sources of data in this study are secondary data and primary data. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the results of the study it is concluded that work motivation and work discipline simultaneously have a significant effect on performance. Work motivation partially has a significant effect on performance. Work Discipline partially has a significant effect on performance.